English usage in daily life by Turkish students between 15–19 years of age: a scale development study. Issue 1 (1st January 2017) - Deha Doğan, C.; Canan Karababa, Z.; Fulya Soğuksu, A.
Abstract: The purpose of this study is to develop a valid and reliable scale to assess the level of English usage in daily life by students between 15 and 19 years of age, and to compare these students' scale scores according to their achievement levels in an English course. Five hundred and ninety-five participants were randomly selected from a universe. Exploratory factor analysis results indicate that the scale has a two-factor structure, which explains 50.1% of the total variance. Exploratory factor analysis is validated by confirmatory factor analysis (NNFI: 0.97; CFI: 0.97; GFI: 0.87; AGFI: 0.84; RMSEA: 0.07; and Standardized RMR: 0.05). Cronbach Alpha coefficients for Factor 1 and Factor 2 were calculated as 0.90 and 0.86, respectively. Test–retest reliability coefficient of the scale is at the expected level (r: 0.86, p<0.001). Item discrimination results indicate that the upper 27% of participants have higher mean rank scores for each item on the scale and on the two factors, and that this difference is significant at the 0.01 level. Results of the study show that students' level of English usage in their daily life is low, and that the students who use more English in their daily life have a higher achievement level in the English course.